WhatsApp and false information: a value-oriented evaluation - Puska, Alisson; Baroni, Luiz Adolpho; Canal, Maíra Codo; Piccolo, Lara S. G.; Pereira, Roberto (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Disseminated mainly through social media, online false information has triggered alarming negative impact on all aspects of life including politics, science, and education. In Brazil, WhatsApp has been pointed out as one of the main vehicles for disseminating false information, reaching millions of people all across the country. This paper presents an evaluation on WhatsApp with a values-oriented approach to investigate what aspects of this platform contributed to the false information spread in Brazil. The evaluation was conducted with 6 WhatsApp heavy users in a 2-hour session, identifying 16 different problems. Results revealed aspects of the technical infrastructure and user interface that influence the way different stakeholders can use the tool to promote false information. Finally, the paper presents prospective paths for improvements on the platform and possible ways to deal with the identified problems.